(untitled) (Revista Justiça do Direito, 2022)
Using Leonel Severo Rocha’s pragmatic-systemic theory, the present work approaches society as communication. It was discoursed about the categories "communication", "mass media", "public opinion" and "protest movements". The respective categories of Luhmannian theory were applied taking into account the AIDS epidemic and the respective attribution of HIV virus contamination to homosexuality. In the first cases of the disease, the mass media used sensationalist information, causing misinformation about AIDS. Homosexuals who were already stigmatized by their own sexual orientation served as "scapegoats", and the disease for decades was called "gay cancer".